SENYAWA ANTIMAKAN TERHADAP Epilachna Sparsa DARI BATANG GAYAM (Inocarpus fagiferus Fosb.) - I M. Sukadana; S. R. Santi; N. N. T. Hanayanthi (Jurnal Kimia (Journal of Chemistry), 2020)
Epilachna sparsa is one of the plant pests that damage the epidermal layer on the bottom side of the leaves, so it can lead to damage of leaf tissue and only the skeleton remains. Gayam (Inocarpus fagiferus) is one of the species of the Legumineceae family which has insecticide activity. This study aims to isolate and identify the antifeedant triterpenoid compound from stem of gayam (Inocarpus fagiferus Fosb.) against Epilachna sparsa larvae. Dried powder of 1200 g gayam stems produced 17.82 g of crude methanol extract with antifeedant activity of 60.74% at a concentration of 5% (w/v) which was further separated by partition to obtain n-hexane, ethyl acetate, and water extracts. Extracts of n-hexane, ethyl acetate, and water at 5% (w/v) concentration showed antifeedant activity of 46.74%, 18.09%, and 8.31% respectively. Futhermore, the most active n-hexane extract was identified by phytochemical tests and LC-MS/MS. The phytochemical test showed n-hexane extract contains triterpenoid compounds. The mass spectra from LC-MS/MS chromatogram peaks with MassLynx V4.1 software and Chemspider database for n-hexane extracts which were previously purified by SPE (Solid method) Phase Extraction) using methanol and dichloromethane (DCM) eluents show the presence of components of flavonol pyrogallol, sucrose2,3,3 ', 4', 6-pentaacetate, soyasaponin I, and a compound with a molecular weight of 685,225 g/mol which cannot be identified further because there is no match spectra with the database. Keywords: antifeedant, Epilachna sparsa, gayam, Inocarpus fagiferus Fosb., triterpenoid.